(untitled) (Sebha University Conference Proceedings, 2022)
The current research paper aims to highlight the dangers that Libyan children are exposed to as a result of armed conflicts since (2011) until the present time, the most important of which is recruitment within armed brigades as a form of security corruption. This situation resulted in stripping children of their innocence as they have the right to grow up in a Safe and stable climate. The paper also aims to clarify the negative psychological and social repercussions that may result from security corruption during crises and armed conflicts. Such an issue of corruption requires immediate intervention to protect children from the effects of armed conflicts and achieve human security in society. The study relied on the descriptive approach and the extrapolation of previous studies related to the subject at hand. It reached many results, the most important of which is the association of armed conflicts with many forms of corruption. Perhaps the most important of which is security corruption, and the culture of violence, as such practices have become in light of armed conflicts, as indicated by the studies It indicates that there is a strong positive relationship between child labor and the environment of wars and armed conflicts, based on the main determinants of child labor in the Arab region, which confirmed that this phenomenon arises in societies suffering from crises and associated traumas such as wars and armed conflicts. Among the recommendations, the most important of which are: immediate intervention to protect children from the effects of armed conflicts, work to withdraw this sector of children from armed brigades, and shelter them in state institutions in order to contain these children and return them to their schools and qualify them in all aspects.